THE IMPLEMENTATION OF INSPIRED TBLT FRAMEWORK IN ENHANCING STUDENTS’ ENGAGEMENT - Irfan Fajrul Falah; Didi Suherdi; Ahmad Bukhori Muslim (Eltin Journal : Journal of English Language Teaching in Indonesia, 2023)
Students’ engagement is essential in enhancing quality of learning experiences. In TBLT setting, it has received a little attention from the scholars despite it is an approach where the students participation actively during task completion. This article reports a study of students’ engagement where inspired-TBLT framework was implemented in speaking class. The research methodology that employed by the author in the current study was a micro ethnography study which describe, interprets the value, behavior and students’ beliefs. The participants were 46 EFL learner in a private university in Indonesia consisted of 30 females and 16 males. That data was collected through a questionnaire adapted from Handelsman’s et al., and semi-structured interview where six students voluntarily take a part in the process. The result of current study shows that inspired-TBLT framework engages the students in speaking class. Three types of engagement -behavioral, emotional, and cognitive- were existed during the implementation of the framework. Behavioral engagement can be identified from participate actively in a discussion, asking a question, students’ attendance and completing the homework given. Meanwhile, the emotional engagement was seen from students’ desire, students’ confidence and doing well on the test. The last but not least, students’ cognitive engagement reflected from applying course to students’ life, finding ways to make course interesting and doing some strategies to improve learners’ speaking skills.